THE INFLUENCE OF TURBOLITY ON LASER SIGNALS: THE INFLUENCE OF TURBOLITY ON LASER SIGNALS - Yanchev, Kiril (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The subject of the research is to make a correct assessment of the vibrations and to choose a model for their elimination, which will allow achieving the required accuracy and high productivity with minimal material costs when performing laser measurements.